PENGARUH VARIASI MAINTENANCE AXIAL FAN COOLING TOWER DI PT. GEO DIPA ENERGU DIENG (Jurnal Inovasi Mesin, 2022)
In an effort to overcome the problem of damage to the machine, it is necessary to have a maintenance process, so as to minimize the impact of the damage, repair the damage, and prevent the damage itself. Maintenance is the process of maintaining or caring for an object which aims to ensure the operation of machines, equipment or other assets can be used continuously and efficiently in the long term. According to the results of research conducted by micromain, maintenance can save up to 545% of the return on costs required during maintenance. PT Geodipa Energi, in an effort to prevent greater damage due to damage to the axial fan, carries out maintenance on the axial fan cooling tower. Taking into account various factors, the blades were replaced on several fans and the slope of the blades on the axial fan was corrected. This was done so that the service life of the axial fan increased, the performance was more efficient, and to avoid damage such as the axial fan breaking.